PERGESERAN PARADIGMA AGAMA DAN SAINS DI TENGAH PANDEMI COVID DALAM KACA MATA THOMAS KUHN - Abdul Rosyid (ASKETIK: JURNAL AGAMA DAN PERUBAHAN SOSIAL, 2020)
Nowadays, Corona Virus (Covid-19) affects the inside of fundamental aspects of society. An effort to preventing the pandemic undertaken by all societies. For instance, social and physical distancing, wearing a masker, hand washing is the most important action to prevent viruses. A massive campaign to prevent COVID-19 intensively expressed by the public, instead of affectedby the prevention of act is the religious issues, logic, and science. One obvious example is the prohibition on the use of places of worship, except Mall, public shopping is open. The case that occurs in Indonesia caused a social dilemma in Moslems or other believers in contrast to the government policies. Campaign to the Covid-19 prevention led by the government to present animbalance between policies and public rules. This research tries to examine the theory by which two concepts which is logic opportunity structure and mass structure mobilization proposed by Thomas Kuhn. Therefore, the model of social mobilization and government policies is an object to get the proper description to results in an obvious solution.